Professional Performance and Methodological Training of Future Musical Art Teachers: A Theoretical Approach - Lobova, Olga; Ustymenko-Kosorich, Olena; Zavialova, Olga; Stakhevуch, Oleksandr (Journal of History Culture and Art Research, 2020)
The problem of improving the effectiveness of performance and methodological training is one of the leading in the system of professional development of future teachers of music in higher education institutions. In this regard, the purpose of the article is to study the theoretical foundations of professional performance (vocal, instrumental) and methodological training of future musical art teachers. To achieve this goal, the following methods have been used: generalization of scientific resources, analysis of practical experience, and theoretical modeling. The performance training includes the organization of the students’ work with the main instrument and voice production (during individual classroom and independent activities, in the class of the ensemble, orchestra, and choir, etc.). Methodological training is the most dynamic feature of the formation of future teachers of music art, due to active changes in regulations and trends in the field of “art”. The prerequisite for the effective provision of professional training for future teachers is the integrated use of several systematically combined approaches. For vocal and instrumental training of music students, these approaches are personality-oriented, individual, and developmental, and for methodological training – competency, culturological, integration, and system approaches. Thus, the performance training of future music teachers is based on scientific approaches to personal orientation, and methodological approaches related to modern requirements and pedagogical trends in general secondary education.